Japanese culture in modern Malay literature: experiences and observations of Malay writers - Che Man, Siti Hajar; Ab. Razak, Ratna Roshida (Dewan Bahasa dan Pustaka, 2015)
This article aims to examine the beauty of the values still adhered to in Japanese society as traceable in creative works based on the experiences and observations of Malay writers. Values such as beauty, silence, refinement, internal strength and civilized living have been adapted from the ontological transformations and pathetic beauty inherited from the glory days of Matsuo Basho (1644-1694) and Yasunari Kawabata (1899-1972). This study draws on the cultural studies theory of Chris Barker. The discussion is centred on the experiences of several Malay writers who have fictionalized their experiences of life in Japan. Muhammad Haji Salleh follows Basho’s footsteps and is inspired by a love for nature and the soul and character of the Japanese, as recorded in his poems in the anthology Salju Shibuya (The Snows of Shibuya), while Arena Wati delves into the national pride and social history of the Japanese and Malays in his novel Sakura Mengorak Kelopak (The Sakura Sheds its Petals), and Abu Yazid Abidin shares the ups and downs of immigrant Malays in Japan in his own novel, Sejuk-sejuk Tokyo (Frosty Tokyo).